Nutrition Support and Tight Glucose Control in Critically Ill Children: Food for Thought! - Vijay Srinivasan; Vijay Srinivasan (Frontiers Media S.A., 2018)
Numerous studies have examined the strategy of tight glucose control (TGC) with intensive insulin therapy (IIT) to improve clinical outcomes in critically ill adults and children. Although early studies of TGC with IIT demonstrated improved outcomes at the cost of elevated hypoglycemia rates, subsequent studies in both adults and children have not demonstrated any benefit from such a strategy. Differences in patient populations, variable glycemic targets, and glucose control protocols, inconsistency in attaining these targets, heterogeneous intermittent sampling, and measurement techniques, and variable expertise in protocol implementation are possible reasons for the contrasting results from these studies. Notably, differences in modes of nutrition support may have also contributed to these disparate results. In particular, combined use of early parenteral nutrition (PN) and a strategy of TGC with IIT may be associated with improved outcomes, while combined use of enteral nutrition (EN) and a strategy of TGC with IIT may be associated with equivocal or worse outcomes. This article critically examines published clinical trials that have employed a strategy of TGC with IIT in critically ill children to highlight the role of EN vs. PN in influencing clinical outcomes including efficacy of TGC, and adverse effects such as occurrence of hypoglycemia and hospital acquired infections. The perspective afforded by this article should help practitioners consider the potential importance of mode of nutrition support in impacting key clinical outcomes if they should choose to employ a strategy of TGC with IIT in critically ill children with hyperglycemia.